Epidemiological Analysis of Human Q fever in Spain (2020-2024) (Boletín Epidemiológico Semanal, 2025)
Introduction: Q fever is caused by Coxiella burnetii, a highly infectious and resistant bacterium. Spain notifies the highest number of cases in Europe.Method: A descriptive analysis of autochthonous cases notified to RENAVE in the 2020-2024 period. Variables of person, place and time were analysed by calculating frequencies, percentages and notification rates (NR). Disease maps were generated.Results: In 2024, 544 cases were notified (NR= 1.12), both maximum values for the period 2020-2024. Seasonality shifted, with increased cases in January and February. Andalusia notified the highest number of cases and Navarre the highest NR.Discussion: The increase of cases is likely related to improved disease notification. Men over 45 years old are occupationally at-risk. A One Health approach is recommended.
Keywords: Q fever; Coxiella burnetii; zoonoses; epidemiological surveillance; Spain